Phenylalanine Increases the Production of Antioxidant Phenolic Acids in Ginkgo biloba Cell Cultures - Agnieszka Szewczyk; Inga Kwiecień; Mariusz Grabowski; Karolina Rajek; Emilia Cavò; Maria Fernanda Taviano; Natalizia Miceli (Molecules, 2021)
The aims of this study were to evaluate the antioxidant properties, to investigate the content of major secondary metabolites in Ginkgo biloba cell cultures, and to determine the change in the production of phenolic acids by adding phenylalanine to the culture medium. Three in vitro methods, which depend on different mechanisms, were used for assessing the antioxidant activity of the extract: 1,1-diphenyl-2-picrylhydrazil (DPPH), reducing power and Fe2+ chelating activity assays. The extract showed moderate activity both in the DPPH and in the reducing power assays (IC50 = 1.966 ± 0.058 mg/mL; ASE/mL = 16.31 ± 1.20); instead, it was found to possess good chelating properties reaching approximately 70% activity at the highest tested dose. The total phenolic, total flavonoid, and condensed tannin content of G. biloba cell culture extract was spectrophotometrically determined. The phenolic acid content was investigated by RP-HPLC, and the major metabolites—protocatechuic and p-hydroxybenzoic acids—were isolated and investigated by 1H NMR. The results showed that phenylalanine added to G. biloba cell cultures at concentrations of 100, 150, and 200 mg/150 mL increased the production of phenolic acids. Cultures that were grown for 3 weeks and collected after 4 days of phenylalanine supplementation at high concentration showed maximal content of phenolic acids (73.76 mg/100 g DW).